Career Management Programmes for Academics in the Higher Education Sector: A RE-AIM Systematic Review - Barnes, N.; Du Plessis, M.; Frantz, J. (South African Journal of Higher Education, 2021)
Academic career development is a fundamental strategy for higher education institutions to achieve strategic objectives and in turn, critical for the achievement and sustainability of national priorities. While the value of a career management strategy is agreed and various normative designs for career management systems have been identified, there is no comprehensive career management approach to provide a framework for the successful management of academic careers across the various career stages. The aim of this study was therefore to systematically review the empirical research recorded on academic career development programmes that could inform and support the development of a structured career management framework for academics. A systems thinking framework (STF), which identifies the individual, social and socio-environment as the key systems, was used to categorise and thematically examine the sample articles which formed part of the study. While the STF recognises the individual as central to the career development process, the predominant programmes are constructed in the social system, with a clear focus on what institutions could do to support the career trajectory of academics. These programmes include coaching and mentoring for early career academics, together with the development of academic writing skills. Minimal research that explicitly describes the interaction and inseparability of these systems as a central construct of the STF is found. There is also no clear evidence of how the higher education context within the socio-environmental system is considered and captured during the management of academic careers. This article concludes by identifying critical considerations for the development of an academic career management framework.